2004
DOI: 10.1007/s11167-005-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of willemite by modified sol-gel technique

Abstract: Silicate luminophor Zn 2 SiO 4 : Mn was synthesized using silica gel as an active form of silicon dioxide. Factors affecting the degree of crystallinity of the silicate obtained were studied. Willemite was doped with manganese(II) in the course of synthesis. The luminescence parameters of the resulting samples were estimated.The synthesis of luminophors for various applications and the improvement of their working parameters constitute one of the most topical problems of the technology of functional materials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Usually, doped willemite is synthesized by the solid-phase technique i.e. by sintering a mixture of the appropriate oxides with silica at a temperature of about 1300-1350 1C for around 10 h [45]. This process is very energy consuming compared to our method that allowed the synthesis in 1 h at 800-1000 1C.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Usually, doped willemite is synthesized by the solid-phase technique i.e. by sintering a mixture of the appropriate oxides with silica at a temperature of about 1300-1350 1C for around 10 h [45]. This process is very energy consuming compared to our method that allowed the synthesis in 1 h at 800-1000 1C.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Cu 9 Sb 4 O 19 hasb een referred to in severald ifferent studies but no further investigation has been done following from Shimada's work on this complex oxide even thoughn os tructural solution has been produced. [11][12][13][14] The solid-solution Cu 2 + x Ti 2-x Fe 2-x Sb x O 9 having ab ixbyite-type structure was homogenous over the range of x = 0t o1 .4, requiringa no xygen atmosphere to synthesise the copper/antimony rich end of the solution.Bye xtrapolation, the end of the solution was calculated to be Cu 4 Sb 2 O 9 with a ' 9.62 .M ouron et al identified that this could be the same oxide identified as Cu 9 Sb 4 O 19 by Shimada et al and believed that the structure of the oxide was likely closely related to the bixbyite type. [12] Bazuev rationalized this solid-solution by suggesting the notion of ad ouble substitution of cations, from Ti 4 + + Fe 3 + for Cu 2 + + Sb 5 + .…”
Section: Introductionmentioning
confidence: 99%
“…12 O método de síntese mais amplamente utilizado na obtenção destes materiais é a reação no estado sólido, o qual exige grande quantidade de energia e tempo. 10 A utilização da técnica sol-gel em substituição às reações de estado sólido começou a ser avaliada nos últimos anos, [13][14][15] apresentando inúmeras vantagens: alta cristalinidade, partículas de pequeno tamanho, homogeneidade da matriz e agentes ativadores, alta e eficiente luminosidade e ausência de fases não luminosas. 13 Estas particularidades do método serão discutidas neste trabalho.…”
Section: Introductionunclassified
“…10 A utilização da técnica sol-gel em substituição às reações de estado sólido começou a ser avaliada nos últimos anos, [13][14][15] apresentando inúmeras vantagens: alta cristalinidade, partículas de pequeno tamanho, homogeneidade da matriz e agentes ativadores, alta e eficiente luminosidade e ausência de fases não luminosas.…”
unclassified